2019
DOI: 10.1016/j.nicl.2019.101776
|View full text |Cite
|
Sign up to set email alerts
|

GABA and glutamate moderate beta-amyloid related functional connectivity in cognitively unimpaired old-aged adults

Abstract: Background Effects of beta-amyloid accumulation on neuronal function precede the clinical manifestation of Alzheimer's disease (AD) by years and affect distinct cognitive brain networks. As previous studies suggest a link between beta-amyloid and dysregulation of excitatory and inhibitory neurotransmitters, we aimed to investigate the impact of GABA and glutamate on beta-amyloid related functional connectivity. Methods 29 cognitively unimpaired old-aged adults (age = 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 94 publications
1
30
0
Order By: Relevance
“…Severe deficits in the cholinergic system have been linked to AD, and cholinergic neurons in the nucleus basalis of Meynert have been identified as a progression marker of cognitive decline in AD (Whitehouse et al ; Whitehouse et al ). Other neurotransmitter systems, including NE, serotonin, glutamate, and somatostatin, are believed to contribute to the disease (Esposito et al ; Solarski et al ; Park et al ; Quevenco et al ; Metaxas et al ). Currently, no effective therapeutics are available to either halt or reverse the progression of AD that is likely because of its polygenic nature (Gold ).…”
Section: Dβh In Neurodegenerative Diseasementioning
confidence: 99%
“…Severe deficits in the cholinergic system have been linked to AD, and cholinergic neurons in the nucleus basalis of Meynert have been identified as a progression marker of cognitive decline in AD (Whitehouse et al ; Whitehouse et al ). Other neurotransmitter systems, including NE, serotonin, glutamate, and somatostatin, are believed to contribute to the disease (Esposito et al ; Solarski et al ; Park et al ; Quevenco et al ; Metaxas et al ). Currently, no effective therapeutics are available to either halt or reverse the progression of AD that is likely because of its polygenic nature (Gold ).…”
Section: Dβh In Neurodegenerative Diseasementioning
confidence: 99%
“…Some studies have suggested that the loss of balance of excitatory versus inhibitory neurotransmitter systems may underline early cognitive deficits and occasional epileptiform activity in AD (Goutagny et al, 2013; Petrache et al, 2019; Stoiljkovic, Kelley, Horvath, & Hajos, 2018; Vossel et al, 2016). The imbalance of glutamatergic and GABAergic neurotransmission may also be interrupted by oAβ (Quevenco et al, 2019). This and other evidence support an imbalance between excitatory and inhibitory transmission that may contribute to cognitive deficits in AD patients (Selten, van Bokhoven, & Nadif Kasri, 2018; Vico Varela, Etter, & Williams, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The wide spread loss of GABA levels shown in these studies may simply be related to AD-associated neuronal loss. A recent study has shown that alteration of functional brain networks in AD are more related to GABAergic dysfunction than glutamatergic dysfunction in humans 62 . In an APPxPS1 mouse model of AD, Jo et al .…”
Section: Discussionmentioning
confidence: 99%